Developing and sustaining digital professionalism: a model for assessing readiness of healthcare environments and capability of nurses. Issue 1 (31st October 2019) - Mather, Carey Ann; Cummings, Elizabeth
Abstract : Introduction: Technological change in healthcare demands new ways of working. Access to, and use of, digital technology by nurses in Australia lags behind other professions. Governance frameworks and professional standards guide scopes of practice; however, there is an urgent need for current registered nurses to master using digital technology and model digital professionalism to the next generation. Sustaining digital professionalism requires organisational readiness to accommodate changing technological environments. Methods: Previous original research findings investigating the nature and scope of digital technology use by nurses were systematically analysed. With reference to current understandings of capability, a matrix for assessing organisational readiness of capability of digital technology use by nurses was developed. Results: The 4E3P digital professionalism model articulates the elements necessary for establishing organisational readiness and assessing the capability development of individuals and groups. When the physical and social environment is conducive and the 4E elements of equipment, electronic access, engagement and education are present, preparedness, proficiency and professional behaviours can be nurtured and supported. Discussion: The model describes the physical and social attributes that enable capability development for sustaining digital professionalism to advance nursing practice. When elements of the matrix are lacking, both individuals and groups miss opportunities to develop and sustain digitally professional behaviour. Conclusion: It is imperative that healthcare environments in Australia support the development of digital professionalism. Deployment of the 4E3P digital professionalism model will enable identification and remediation of challenges, barriers or risks to promote sustainability found within physical and social healthcare environments.